2017
DOI: 10.1016/j.jid.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Controlled Trial Evaluating a Cx43-Mimetic Peptide in Cutaneous Scarring

Abstract: The transmembrane protein Cx43 has key roles in fibrogenic processes including inflammatory signaling and extracellular matrix composition. aCT1 is a Cx43 mimetic peptide that in preclinical studies accelerated wound closure, decreased inflammation and granulation tissue area, and normalized mechanical properties after cutaneous injury. We evaluated the efficacy and safety of aCT1 in the reduction of scar formation in human incisional wounds. In a prospective, multicenter, within-participant controlled trial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 59 publications
2
51
0
Order By: Relevance
“…8,15,29,30 Consistent with preclinical observations, a Phase II clinical trial determined that αCT1 improved scar visual appearance by 47% 9 months post-surgery relative to within-patient controls following laparoscopic surgery. 31 This long-term improvement showed a trend of progressive emergence over the study period, with a modest 12.9 % augmentation over control observed at 3 months, but no apparent difference between αCT1 and control scars at 1 month. In the present study, we took advantage of an earlier vehicle-controlled Phase I clinical trial evaluating the safety and tolerability of αCT1 involving 49 healthy subjects in which scar tissue was biopsied from the wound site 29 days following cutaneous injury.…”
Section: Introductionmentioning
confidence: 74%
“…8,15,29,30 Consistent with preclinical observations, a Phase II clinical trial determined that αCT1 improved scar visual appearance by 47% 9 months post-surgery relative to within-patient controls following laparoscopic surgery. 31 This long-term improvement showed a trend of progressive emergence over the study period, with a modest 12.9 % augmentation over control observed at 3 months, but no apparent difference between αCT1 and control scars at 1 month. In the present study, we took advantage of an earlier vehicle-controlled Phase I clinical trial evaluating the safety and tolerability of αCT1 involving 49 healthy subjects in which scar tissue was biopsied from the wound site 29 days following cutaneous injury.…”
Section: Introductionmentioning
confidence: 74%
“…The biochemical characterizations indicated that αCT1 is capable of two distinct protein-protein interactions -one with ZO-1 PDZ2 and the other with the Cx43 H2 region. This raised the question as to whether or not the previously characterized effects of αCT1 in cardiac injury models 11,12 , or indeed its wound healing effects at large [16][17][18]24 , could be accounted for by one or another of these protein-protein interactions. The series of αCT1-based variant peptides generated for the present study provided an opportunity to address this question.…”
Section: Only Peptides Interacting With Cx43 Ct Protect Hearts From Imentioning
confidence: 99%
“…The details of αCT1 molecular mechanism is of key translational significance as this therapeutic peptide is presently the subject of testing in the clinic 15 . In Phase II clinical trials, αCT1 showed efficacy in promoting the healing of two types of chronic, slow healing skin wounds [16][17][18] . αCT1 is currently in Phase III testing on more than 500 patients, as a treatment for diabetic foot ulcers (GAIT1 trial) 19 .…”
Section: Introductionmentioning
confidence: 99%
“…61 While the exact mechanism of action remains unknown, Cx43 has been known to a regulate transforming growth factor beta (TGF-b) signaling, a marker of fibrosis. 61 Early human trials saw relative success of the material in reducing scar formation following surgery 62 and healing diabetic foot ulcers. 63 Phase 3 clinical trials are ongoing to evaluate the efficacy of this material in diabetic chronic foot ulcers.…”
Section: Scar Minimizationmentioning
confidence: 99%